INTEGRATING YOGA AND MINDFULNESS IN PERFORMING ARTS EDUCATION - Supriya S. Patil; Raikwar, Rajesh; Bhan, Suraj; Karthick, Arumugam; Kariveliparambil, Ashifa; Chanakar, Vaibhav (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Education in arts is important in the development of creativity, arts expression and communication of culture. Nevertheless, the conventional training of performing arts tends to emphasize more on the development of technical skills and the preparation of performance to the exclusion of the physical and psychological health of performers. This study examines how yoga and mindfulness can be incorporated in the process of performing arts education as a comprehensive strategy towards ensuring the development of the performers. This paper investigates how mind-body techniques enhance physical training, mental concentration, emotional, and creative expression in the performing artists. An integrated model is suggested that integrates yoga-driven bodily training and mindfulness-driven mental training in aiding the development of whole performers. The framework incorporates the important elements of yoga practice to ensure the flexibility and posture management, mindfulness meditation to focus the mind, breathing to regulate the emotions, and reflections to explore the creativity in a creative way. The comparison of traditional performing arts training and mindfulness-based training is made through a number of evaluation parameters such as physical conditioning, mental focus, emotional, regulation, creativity, and wellness of the performers. The findings show that yoga and mindfulness practitioners are significantly better in their concentration, emotional stability, confidence on the stage, and well-being than those participants who use conventional training programs. Future research directions (including integrating digital learning, AI-assisted mindfulness training, and using AI in cross-cultural performance arts education) are also addressed in the research. The results suggest that the incorporation of mind-body practices into performing arts curricula is vital to provide more balanced, creative, and sustainable learning opportunities to the performers.